High-energy mid-infrared sub-cycle pulse synthesis from a parametric amplifier - Houkun Liang (Nature Portfolio, 2017)
Stable sub-cycle pulses in the mid-infrared region allow damage-free investigation of electron dynamics in solids. Here, the authors develop a suitable source to this end which is based on an optical parametric amplifier.